Sistemática e paleobiologia de microfósseis de equinodermas da Formação Pirabas (Mioceno inferior), estado do Pará - MONTEIRO, Débora Barroso (2019)
This research deals the data obtained from the analysis of calcareous microfossils in samples collected in Pirabas Formation that occurs at Mina B-17 Cimentos do Brasil S. A., municipality of Capanema and Atalaia beach, Salinópolis municipality, Pará State, and aiming at the systematic and paleobiological characterization. The treatment of the samples reveals 27 fragments of crinoids and 18 fragments of ophiuroids. The ophiuroids are represented by the family Gorgonocephalidae and genus Ophiomusium and Ophiactis (?) and among the fragments of crinoids, were recognized the order Comatulida. The taxonomic composition, living environment and biostratinomic features these echinoderms and other associated faunal elements studied in the lithofacies at Atalaia beach allowed to considere that the fossiliferous concentration is parauthoctonous. The fragments of the echinoderms collected in samples of B-17 Mine characterize a fossiliferous concentration allochthonous where the vertebrae were transported to the lagoon by tidal channels during storms that ravaged the sea Pirabas. The echinofaune studied keep affinity with the miocenic associations of the Caribbean Biogeographic Province, especially with those recorded in Florida, Puerto Rico, Trinidad, Panama, Cuba, Haiti and the Dominican Republic, and the taxa identified corroborate the faunal exchange between regions Eastern Tropical Pacific (PLT) and Tropical Western Atlantic (AOT), already well established in other groups.